Europe's fault lines: racism and the rise of the right - Fekete, Elizabeth (London, 2018)
"An expansive investigation into the relationship between contemporary states and the far-right It is clear that the right is on the rise, but after Brexit, the election of Donald Trump and the spike in popularity of extreme-right parties across Europe, the question on everyone’s minds is: how did this happen?